2014
DOI: 10.1111/psj.12048
|View full text |Cite
|
Sign up to set email alerts
|

New Avenues for the Study of Agenda Setting

Abstract: Existing literature on the agenda‐setting process is grounded and well cited in studies of U.S. national institutions, but emerging scholarship has taken the fundamental principles of agenda setting—attention, information, and learning—and has extended their applicability to understudied participants and institutions. This essay highlights three areas of study that have undergone particular growth during the last few years and best represent the trend of applying the well understood dynamics of agenda setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
0
24
0
2
Order By: Relevance
“…Institutions introduce friction against more efficient, incremental patterns of attention allocation. Without taking into account the issue of context‐specificity in operationalizing institutional friction, it is generally understood that the tendency of attention allocation to punctuate is the dynamical manifestation of minority obstruction realized in one way or another (Eissler, Russell, & Jones, ). Focusing on liberal democracies, Jones et al (, p. 167) argue that democracies may actually be purposively tuned toward “regular disruptions,” entailing processes that are punctuated by occasional “dislocations” but free from the “catastrophe.”…”
Section: Punctuated Equilibrium In Liberal Democracies: Cognitive Andmentioning
confidence: 99%
“…Institutions introduce friction against more efficient, incremental patterns of attention allocation. Without taking into account the issue of context‐specificity in operationalizing institutional friction, it is generally understood that the tendency of attention allocation to punctuate is the dynamical manifestation of minority obstruction realized in one way or another (Eissler, Russell, & Jones, ). Focusing on liberal democracies, Jones et al (, p. 167) argue that democracies may actually be purposively tuned toward “regular disruptions,” entailing processes that are punctuated by occasional “dislocations” but free from the “catastrophe.”…”
Section: Punctuated Equilibrium In Liberal Democracies: Cognitive Andmentioning
confidence: 99%
“…Observing the media-reactive behavior of political actors, this literature strongly suggests that politicians derive information from media coverage and that they profit from the momentum generated by the information to use it in their work. When the media address an issue, politics follows suit and politicians increasingly start to talk about it (Eissler, Russell, & Jones, 2014;Walgrave & Van Aelst, 2006). This literature, falling under the header of "political agenda-setting and the media," has showed that the media affect the political agenda in many countries, both in majoritarian and in proportional democracies (e.g., Bonafont & Baumgartner, 2013;Edwards & Wood, 1999;Soroka, 2002;Van Noije, Oegema, & Kleinnijenhuis, 2008;Walgrave, Soroka, & Nuytemans, 2008).…”
Section: The Information Functionmentioning
confidence: 99%
“…We aim to cycle review articles within each substantive area listed in the Yearbook approximately every 3 years. In five of the policy research areas categorized in the Yearbook, we have now cycled two articles, written 3 years apart: policy process theories (Nowlin, 2011, Petridou, 2014, policy analysis (Blume, Scott, & Pirog, 2014;Carlson, 2011), agenda setting (Eissler, Russell, & Jones, 2014;Pump, 2011), public opinion and public policy (Bachner & Hill, 2014;Mullinex, 2011), and education policy (Conner & Rabovsky, 2011;Galey, 2015).…”
Section: S6mentioning
confidence: 99%